The contribution of mitochondrial DNA alterations to aging, cancer, and neurodegeneration - Picca, Anna; Guerra, Flora; Calvani, Riccardo; Coelho-Júnior, Hélio José; Leeuwenburgh, Christiaan; Bucci, Cecilia; Marzetti, Emanuele (Experimental gerontology, 2023)
Mitochondrial DNA (mtDNA) is as a double-stranded molecule existing in hundreds to thousands copies in cells depending on cell metabolism and exposure to endogenous and/or environmental stressors. The coordination of mtDNA replication and transcription regulates the pace of mitochondrial biogenesis to guarantee the minimum number of organelles per cell. mtDNA inheritance follows a maternal lineage, although bi-parental inheritance has been reported in some species and in the case of mitochondrial diseases in humans. mtDNA mutations (e.g., point mutations, deletions, copy number variations) have been identified in the setting of several human diseases. For instance, sporadic and inherited rare disorders involving the nervous system as well higher risk of developing cancer and neurodegenerative conditions, including Parkinson's and Alzheimer's disease, have been associated with polymorphic mtDNA variants. An accrual of mtDNA mutations has also been identified in several tissues and organs, including heart and muscle, of old experimental animals and humans, which may contribute to the development of aging phenotypes. The role played by mtDNA homeostasis and mtDNA quality control pathways in human health is actively investigated for the possibility of developing targeted therapeutics for a wide range of conditions. •Mitochondrial DNA (mtDNA) is a multi-copy genome varying with cell metabolism and stressors.•Heteroplasmic and homoplasmic mtDNA mutations contribute to several disease conditions.•Sporadic and inherited rare disorders of the nervous system hold mtDNA mutations.•Accrual of mtDNA mutations has been reported in several tissues during aging.•mtDNA mutations are implicated in tumorigenesis.